CURRICULUM DEVELOPMENT MANAGEMENT IN IMPROVING THE ABILITY TO READ THE QUR'AN IN QURAN HADITH LESSONS AT MTs TAMAN PENDIDIKAN ISLAM MEDAN - Amin, Askur; Azmi, Fachruddin; Neliwati, Neliwati (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to analyze curriculum development management in improving the ability to read the Koran in Quran Hadith lessons at MTs Taman Pendidikan Islam Medan. This research is a type of qualitative research using a descriptive approach. In gathering this information, the researcher will carry out observations and interviews with the head of the Madrasah, deputy head of the Madrasah for Curriculum, and teachers and other parties concerned with this research. The research results concluded that planning for Al-Quran learning at MTs TPI Medan was carried out by each teacher when teaching, including the annual program, semester program, syllabus and learning implementation plan (RPP). The organization of Al-Quran learning is under the coordination of the Al-Quran Sector, namely for students who cannot yet read the Al-Quran by holding remedial Iqra classes, while enrichment activities for Al-Quran learning are for students who can read the Al-Quran fluently through Tahfiz Al-Quran classes combined with recitations. In implementing Al-Quran learning in the Integrated Class at MTs TPI Medan, teachers use various methods, group learning models, utilizing standard learning media such as markers and whiteboards, textbooks to laptops and multimedia. Evaluation of Al-Quran Learning in the Integrated Class at MTs TPI Medan, including students' daily morals and/or morals that are in accordance with the learning material. Evaluations are also carried out daily, monthly, mid-semester and semester